Ditopic pyridyl-benzothiazole – Pyridylmethylene-2-thiohydantoin conjugates: Synthesis and study in complexation with CuCl2. (15th July 2022) - Chorbu, Alexander A.; Barskaya, Elena S.; Moiseeva, Anna A.; Guk, Dmitry A.; Krasnovskaya, Olga O.; Lyssenko, Konstantin A.; Rzheutski, Artem V.; Abramovich, Maksim S.; Polyakova, Margarita N.; Berezina, Anna V.; Zyk, Nikolai V.; Beloglazkina, Elena K.
Graphical abstract: New ditopic ligands with of 2-(2-pyridyl)benzothiazole and 5-pyridylmethylene-2-thioimidazol-4-one moieties linked through polymethylene or triazole-containing linker were synthesized and their coordination properties in the reactions with CuCl2 were studied. Abstract: New ditopic ligands (L) consisting of 2-(2-pyridyl)benzothiazole and 5-pyridylmethylene-2-thioimidazol-4-one moieties linked with polymethylene chains of various lengths (compounds 4 ) or triazole-containing linker (compounds 9, 11 ) were synthesized and their coordination properties in the reactions with CuCl2 were investigated. All the obtained copper complexes had the LCuCl2 composition. Ligands 4 with polymethylene linkers coordinate CuCl2 initially at the 5-pyridylmethylene-2-thioimidazolone moiety, but then copper chloride migrates to the 2-pyridylbenzothiazole fragment. In contrast, ligands 9, 11 with the triazole-containing linkers coordinate CuCl2 at 5-pyridylmethylene-2-thio-imidazolone and triazole fragments, and then the structure of the complex in the solution does not change. In DMF, the initially formed Cu 2+ complexes may be reduced to Cu 1+ compounds, based on electrochemical investigation data.